Management Consultancy and Banking in an Era of Globalization - Jones, A. author. aut Link
X, 213 p.
Keywords: Management consultancy and investment banking have been held up as industries at the forefront of contemporary globalization. Using an inter-disciplinary approach ranging across economics, economic geography, sociology and management studies, Andrew Jones analyzes the nature of globalization within business service transnational corporations in these sectors. Using qualitative research with leading business managers, he focuses on the social and cultural nature of 'doing' global service business in an era of increasing integration of the world economy.